A base of the iterative methodology for a refined determination of electromechanical coupling factors in piezoceramic resonators - Bezverkhyi, O. I.; Zinchuk, L.P.; Karlash, V. L. (Reports of the National Academy of Sciences of Ukraine, 2015)
The grounds of a new computational-experimental iterative methodology that makes it possible to determine electromechanical coupling coefficients and parameters of the energy loss with high precision are described by the example of famous problems of the longitudinal vibrations of a thin piezoceramic rod with transverse polarization and radial oscillations of a thin circular piezoceramic plate with unbroken electrodes.